Analisa Penggunaan E-Wallet dalam Keseharian Masyarakat di Kabupaten Labuhanbatu - Pitryani; Eva Fitria; Elvina (ARBITRASE: Journal of Economics and Accounting, 2022)
Technology that is currently developing can make it easier for people in various ways. One of the conveniences for the community in their daily lives is the use of cash instead of electronic money (e-wallet). The purpose of this study is to get an overview of the use of e-wallets in Labuhanbatu Regency. This research method uses descriptive qualitative with the type of research in the form of case studies in Rantauprapat. The research was conducted from May 2022 to November 2022. The instruments used were a questionnaire given to the public and in-depth interviews (In-depth Interview). The sample in this study is people with an age range of 15 years - 53 years, further distinguished by categories of finance, food and beverages, shopping. Data analysis techniques use the Miles and Huberman methods. Communities in Labuhanbatu Regency have used e-wallets to make online transactions. The most e-wallet users are men with a percentage of 65.56% and women with 34.44%. The age range that uses ¬e-wallet is in the range of 23 years to 30 years (35.56%). 20% for 15-22 years, 20% for 31-38 years, 15.56% for 39-46 years and 8.88% for 46-53 years. Online transactions commonly used by respondents are in the financial category (78%) to pay electricity bills, health insurance, water bills, and other financial transactions. 15% for food purchases and 7% for drinks.